An Open-Source Tool to Facilitate the Processing of GRACE Observations and GLDAS Outputs: An Evaluation in Bangladesh - Purdy, Adam J.; David, Cédric H.; Sikder, Md. Safat; Reager, John T.; Chandanpurkar, Hrishikesh A.; Jones, Norman L.; Matin, Mir A. (Frontiers in Environmental Science, 2019)
Bangladesh lies at the intersection of the Ganges, Brahmaputra, and Meghna rivers with a combined average discharge of 38,000 m3s-1 ranking fourth globally. Despite the volume of water flowing through and seasonally inundating parts of the landscape, groundwater reliance is necessary to support an intensive agricultural industry. Here we use newly-developed open-source software to combine observations from the Gravity Recovery and Climate Experiment (GRACE) satellites with hydrologic estimates of land water storage from the Global Land Assimilation Data System (GLDAS) to isolate basin-scale groundwater anomalies in Northwest Bangladesh from 2002 to 2016. We place our estimates in the context of previously-published water management estimates and our results suggest the largest losses in water storage are due to groundwater abstractions with groundwater storage decreasing at a rate of 0.88 cm yr-1. We estimate basin-averaged total water storage loss from 2002 to 2016 at 27.92 cm with groundwater and surface water storage loss accounting for 12.46 cm or 44.6%. For Bangladesh, a region where 80% of landcover is dedicated for agricultural use and over half of the country’s population is employed in the agricultural sector, the estimated declines in water storage hold long-term implications for the livelihood and food supply of the region.